THE INFLUENCE OF INTERNET JOURNALISM ON POLITICAL PROCESSES - Tokhirova Sevinch Akram kizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: The rapid development of internet journalism has significantly impacted political processes around the world. Through real-time reporting, interactive platforms, and citizen participation, digital media has transformed how political information is disseminated, how public opinion is shaped, and how politicians engage with constituents. This article examines the influence of internet journalism on modern politics, exploring its positive effects—such as increased transparency and civic engagement—as well as challenges like misinformation, political polarization, and manipulation. As online journalism continues to evolve, understanding its political consequences is critical for strengthening democratic institutions and promoting informed participation.